(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of present study was to clarify the links between Executive function and weight-loss. We firstly investigated definition and functions of executive functions and secondly showed studies done in the links. Studies have shown that executive functions can influence on thinking and behaviors, especially, health behaviors. As a result of the preliminary search, the final keywords utilized for the investigation were weight loss, executive functions, obesity and overweight. After that, we found twelve articles and reviewed methods and results of those. The results consisted of three main methods included correlational, experimental methods and ex-post facto studies. In conclusion, present study indicated that executive control as a central control of behavior plays a key role in weight-loss.